2019
DOI: 10.3390/nu11112748
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Metabolism Status, Quality of Life, and Muscle Strength in Older People

Abstract: As the relationship between vitamin D and various diseases or health conditions has become known, interest in the contribution of vitamin D to overall health-related quality of life (QoL) has increased. We examined the relationship between vitamin D status and QoL in 273 participants aged 65 years and older. Serum levels of total calcium, phosphorus, intact parathyroid hormone, albumin, and 25-hydroxyvitaminD3 were analyzed. We also recruited data for QoL, physical activity, nutritional impairment, and muscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
1
8
1
1
Order By: Relevance
“…Besides, vitamin D (Vit D) may play a role between muscle and cognitive function. Vit D deficiency is strongly linked to muscle weakness and loss, suggesting that hypovitaminosis D in the elderly may be an important factor in the development of sarcopenia (Berchtold et al, 2000 ; Lappe and Binkley, 2015 ; Verde et al, 2019 ). It is found that the Vit D receptor is also expressed in the central nervous system (CNS) and that CNS is able to synthetize calcitriol per se due to the expression of the 25-hydroxylase and 1α-hydroxylase, which has raised the hypothesis that Vit D may have a role in brain health and in cognitive performance (D'amelio and Quacquarelli, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, vitamin D (Vit D) may play a role between muscle and cognitive function. Vit D deficiency is strongly linked to muscle weakness and loss, suggesting that hypovitaminosis D in the elderly may be an important factor in the development of sarcopenia (Berchtold et al, 2000 ; Lappe and Binkley, 2015 ; Verde et al, 2019 ). It is found that the Vit D receptor is also expressed in the central nervous system (CNS) and that CNS is able to synthetize calcitriol per se due to the expression of the 25-hydroxylase and 1α-hydroxylase, which has raised the hypothesis that Vit D may have a role in brain health and in cognitive performance (D'amelio and Quacquarelli, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Decorin (DCN) is one of several glycosaminoglycan (GAG) no-collagen proteins secreted by bones. It is characterized as a leucine-rich repetitive core protein in bone [ 60 ]. DCN can directly interact with TGF-β in a dynamic environment to affect cell migration [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between Vit-D and quality of life has also been investigated in different disease populations other than CKD. It was shown that higher Vit-D levels reduced disease activity in patients with ulcerative colitis, and it provided a better muscle strength among patients over the age of 65, thus leading to a better quality of life [37,38]. In another study, it was shown that low 25(OH) D levels were associated with lower physical activity and a weaker mental activity [39].…”
Section: Discussionmentioning
confidence: 99%